Geochemistry of S-type granitic rocks from the reversely zoned Castelo Branco pluton (central Portugal) - Antunes, I. M. H. R. (2008)
The zoned pluton from Castelo Branco consists of Variscan peraluminous S-type granitic rocks. A muscovite>biotite granite in the pluton's core is surrounded successively by biotite>muscovite granodiorite, porphyritic biotite>muscovite granodiorite grading to biotite=muscovite granite, and finally by muscovite>biotite granite. ID-TIMS U-Pb ages for zircon and monazite indicate that all phases of the pluton formed at 310 ± 1 Ma. Whole-rock analyses show slight variation in 87Sr/86Sr310 Ma between 0.708 and 0.712, [var epsilon]Nd310 Ma values between - 1 and - 4 and [delta]18O values between 12.2 and 13.6. These geological, mineralogical, geochemical and isotopic data indicate a crustal origin of the suite, probably from partial melting of heterogeneous Early Paleozoic pelitic country rock. In detail there is evidence for derivation from different sources, but also fractional crystallization linking some of internal plutonic phases. Least-squares analysis of major elements and modelling of trace elements indicate that the porphyritic granodiorite and biotite=muscovite granite were derived from the granodiorite magma by fractional crystallization of plagioclase, quartz, biotite and ilmenite. By contrast variation diagrams of major and trace elements in biotite and muscovite, the behaviours of Ba in microcline and whole-rock [delta]18O, the REE patterns of rocks and isotopic data indicate that both muscovite-dominant granites were probably originated by two distinct pulses of granite magma.